Urinary Exosomes and Their Cargo: Potential Biomarkers for Mineralocorticoid Arterial Hypertension? - Barros, Eric R.; Carvajal, Cristian A. (Frontiers in Endocrinology, 2017)
Arterial hypertension (AHT) currently affects approximately 40% of adults worldwide and its pathological mechanisms are mainly related to renal, vascular and endocrine systems. Steroid hormones as aldosterone and cortisol are highly relevant to human endocrine physiology, and also to endocrine hypertension. Pathophysiological conditions, such as primary aldosteronism (PA), affect approximately 10% of patients diagnosed with AHT and are secondary to a high production of aldosterone, increasing the risk also for cardiovascular damage and heart diseases. Excess of aldosterone or cortisol increases the activity of the mineralocorticoid receptor (MR) in epithelial and non-epithelial cells. Current research in this field highlights the potential regulatory mechanisms of the MR pathway, including pre-receptor regulation of the MR (action of 11BHSD2), MR activating proteins and the downstream genes/proteins sensitive to MR (e.g. ENaC, NCC, NKCC2). Mineralocorticoid AHT is present in 15-20% of hypertensive subjects, but the mechanisms associated to this condition have been poorly described, due mainly to the absence of reliable biomarkers. In this way, steroids, peptides and lately urinary exosomes are thought to be potential reporters of biological processes. This review highlight exosomes and their cargo as potential biomarkers of metabolic changes associated to mineralocorticoid AHT. Recent reports have shown the presence of RNA, miRNAs and proteins in urinary exosomes, which could be used as biomarkers in physiological and pathophysiological conditions. However, more studies are needed in order to benefit from exosomes and the exosomal cargo as a diagnostic tool in mineralocorticoid arterial hypertension.